Morphological analysis of human cortical bone using high-resolution X-ray microtomography - Pirhonen, Jalmari (2012)
Structural and elastic properties of bone are related to microstructural parameters such as porosity and anisotropy. Microtomography (μCT) enables assessment of bone microstructural geometry, typically down to a voxel size of 5 microns. The purpose of this thesis was to evaluate whether using a higher (sub-micrometer) voxel resolution in X-ray μCT enables detection of new, finer, details in human cortical bone. The second objective was to measure several morphological parameters that determine the microstructure, and to compare two different microtomographs. To this end, twenty four human cadaveric femur samples were imaged by Xradia XCT-400 at a voxel size of 0.56 - 0.59 μm and spatial resolution of 1.5 μm. For comparison, samples were measured by Skyscan 1172 at a voxel size of 2.78 μm. Scanner and image reconstruction parameters were individually tuned for each sample, so as to enhance the signal to noise ratio and to increase the amount of small detail. The systematical error due to the chosen procedure was satisfyingly low. Haversian canals (50.8 ± 25.4 μm) and ostecyte lacunae (3.74 ± 0.30 μm) were easily distinguishable from the scans by XCT-400, whereas SkyScan only extracted the Haversian canals. Morphological data from these two microtomographs had consistent distributions at the scale of the Haversian canals. Some correlations were observed between the morphological parameters, e.g. the cortical porosity correlated with pore diameter and number of pores. In conclusion, the Xradia μCT thus enables new level of bone morphological analysis which can enhance the understanding of relations between the properties of hierarchical microstructure and macroscopic features of the bone. Understanding of bone fragility can thereby be enhanced. In particular, such understanding plays important role in developing new methods of non-invasive bone assessment, based on quantitative ultrasound.